PERANCANGAN UI/UX WEBSITE STOK BARANG DISKOMINFO (STOFO) MENGGUNAKAN APLIKASI FIGMA - Vandhira, Via; Lazulfa, Indana; Jauhar Kamilah Basa, Nuriyah; Widoyoningrum, Sri (Inovate, 2025)
The aim of designing the user interface (UI) and user experience (UX) on the stock management website at the Department of Communication and Information (Diskominfo) is to produce a system that is efficient, easy to use, and supports smooth inventory management. This website is named STOFO (Diskominfo Goods Stock System). The Figma application is used in UI/UX design to create a more intuitive and responsive display according to user needs. The design process starts with identifying needs, creating wireframes, interface design, and testing to ensure user comfort. It is hoped that the results of this design can speed up updating and checking stock data and simplify administration at Diskominfo. With a simple and easy to understand design, users can quickly access stock information, thereby increasing efficiency and productivity in inventory management. Keyword : Website Design, UI/UX, Technology